Coronavirus disease of 2019 (COVID-19) in the Gulf Cooperation Council (GCC) countries: Current status and management practices - Thamir A. Alandijany; Arwa A. Faizo; Esam I. Azhar (Elsevier, 2020)
Coronavirus disease 2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is currently a global threat to human population. The numbers of cases and deaths due to COVID-19 are escalating daily, putting health care systems worldwide under tremendous pressure. Policymakers in the affected countries have adopted varying strategies to deal with this crisis. As a result, the current COVID-19 status in terms of number of cases and deaths hugely varies between countries. The Gulf Cooperation Council (GCC) countries have managed to limit the massive spread of the infection among their populations by implementing proactive plans and timely decisions in response to COVID-19 outbreak; measures taken included suspension of flights, closure of educational institutes, curfew and lockdown of major cities, and provision of free-of-charge healthcare to patients. This review summarizes the COVID-19 status as of 18 May 2020 and highlights prevention and control measures applied in the GCC countries.